Positive Solutions to Singular and Delay Higher-Order Differential Equations on Time Scales. (16th August 2009) - Hu, Liang-Gen; Xiao, Ti-Jun; Liang, Jin
Abstract : We are concerned with singular three-point boundary value problems for delay higher-order dynamic equations on time scales. Theorems on the existence of positive solutions are obtained by utilizing the fixed point theorem of cone expansion and compression type. An example is given to illustrate our main result.